Invasive Alien Flora of Sathyamangalam Tiger Reserve in Southern Eastern Ghats, India - Prakash, L.; Balasubramanian, P. (Indian Forester, 2018)
The survey was undertaken to document the invasive alien species distributed in Sathyamangalam Tiger Reserve, Eastern Ghats during November 2014 to November 2016. A total of 107 invasive alien plant species were recorded which belonged to 39 families and 82 genera. Asteraceae formed the most dominant family with 16 invasive alien species, followed by Amaranthaceae (8) and Fabaceae (7). Life-form wise, herbs were the major forms (73.83%) among the invasive alien species. Phytogeographical analysis revealed that species of Tropical American origin formed a major proportion (59.43%) of the invasive alien species in the study area. Monitoring and control of the spread of Prosopis juliflora and Lantana camara is required.